Report on the Survey 2012 amongst doctoral candidates within the Helmholtz Association: Created, carried out and evaluated by the Helmholtz Juniors, the PhD representatives of the Helmholtz Association - Dinto Jose; Ines Thronicker; Martin Seilmayer; Lukas Schmidt (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
[About the Report] The Helmholtz Juniors are the PhD students' network of the German Helmholtz-Association (Helmholtz-Gemeinschaft Deutscher Forschungszentren, HGF). Their main mission is to intensify collaboration between the PhD students of the different Helmholtz research centers and improvement of the PhD education. They consist of elected or delegated members of the PhD representative teams of each center. In order to represent the interest of the PhD1 students at the Helmholtz Association, we need to have precise and up-to-date knowledge about the working conditions, problems and wishes of PhDs. This survey is a crucial basis therefore. After 2008 and 2010, this report refers to the third wave of the Helmholtz wide PhD survey. Its results technically enable us to even describe developments over the last 4 years, which should be the aim of a separate, comprehensive report in the near future. Within the Helmholtz-Juniors, the working group PhD-Survey developed, conducted, analyzed, and reported the survey and its data. The raw data is hold by the working group. The report is free to be used by the Helmholtz Centers as well as their PhDs. In the report, the centers are coded by random ID numbers. According to our data protection policy, each center could be provided with only their ID number. In the report, firstly we provide information about the background of the participants. Secondly we address four main topics of interest, namely PhD project planning, the income situation of PhD students, conditions for starting a family during the time as PhD student and the situation of students of foreign nationalities within the HGF. And thirdly we report results regarding the Helmholtz graduate schools. We do neither refer to every question in the survey nor do we present cross tables or in depth information. If one is interested in further analysis, she may contact the members of this working group. The complete questionnaire is appended.
Keywords: 330